Cistem failure : essays on blackness and cisgender - Bey, Marquis (Asterisk (Duke University Press), 2022)
"In Cistem Failure Marquis Bey meditates on the antagonistic relationship between blackness and cisgender. Bey asks what does it mean to have a gender that "matches" one's sex, that is, cisgender, when decades of feminist theory have destroyed the belief that there is some natural way to be a sex? Moving from the The Powerpuff Girls to the greeting "how ya mama'n'em" to their own gender identity, Bey finds that cisgender is too flat of a category to hold the myriad ways that people-who may not have undergone gender affirmative interventions-depart from gender alignment. At the same time, blackness, they contend, strikes at the heart of cisgender's invariable coding as white: just as transness names a non-cis space, blackness implies a non-cis space. By showing how blackness opens up a way to subvert the hegemonic power of the gender binary, Bey makes a case for an antiracist gender abolition project that rejects cisgender as a regulatory apparatus"--